Leading for Safety: A Question of Leadership Focus - Malin Mattson Molnar; Ulrica Von Thiele Schwarz; Johnny Hellgren; Henna Hasson; Susanne Tafvelin (Elsevier, 2019)
Background: There is considerable evidence that leadership influences workplace safety, but less is known about the relative importance of different leadership styles for safety. In addition, a leadership style characterized by an emphasis and a focus on promoting safety has rarely been investigated alongside other more general leadership styles. Methods: Data were collected through a survey to which 269 employees in a paper mill company responded. A regression analysis was conducted to examine the relative roles of transformational, transactional (management-by-exception active; MBEA), and safety-specific leadership for different safety behavioral outcomes (compliance behavior and safety initiative behaviors) and for minor and major injuries. Results: A safety-specific leadership contributed the most to the enhanced safety of the three different kinds of leadership. Transformational leadership did not contribute to any safety outcome over and above that of a safety-specific leadership, whereas a transactional leadership (MBEA) was associated with negative safety outcomes (fewer safety initiatives and increased minor injuries). Conclusion: The most important thing for leaders aiming at improving workplace safety is to continuously emphasize safety, both in their communication and by acting as role models. This highlights the importance for leadership training programs aiming to improve safety to actually focus on safety-promoting communication and behaviors rather than general leadership. Furthermore, an overly monitoring and controlling leadership style can be detrimental to attempts at achieving improved workplace safety. Keywords: Injury, Leadership, Safety compliance, Safety initiative, Workplace safety